Peranan Perempuan Banjar Dalam Pendidikan Islam Abad XIX dan XX - dan Ahdi Makmur, Salasiah (Muadalah, 2015)
Based on the family culture in South Kalimantan which is patriarchy. men have the privilege more than that of women. South Kalimantan is an area predominantly occupied by Muslim. Since the arrival of Islam in South Kalimantan around the 16th century brought about by the Sultanate of Demak via trade, Banjarmasin kingdom turned into a patterned Islamists led by Sultan Suriansyah with governance structures that are influenced by Javanese culture. Java whose sensible patriarchal culture considered the women at that time onlyas a supplement and concubines to men. In addition, gender inequality and patriarchal culture are deeply rooted in the cultural traditions of Banjar. Growing view in society about women makes them do not take part freely in the public domain. Public already believes that women can take part only in the privacy of the home environment. Few female characters are written in this study with the aim to open up the idea that Banjarese women are intelligent, able to provide imaging of the women, who have equivalent education to men, and are capable of acting to contribute energy and thoughts on public space in the field of education.